Nutrients, dietary supplements, and nutriceuticals : cost analysis versus clinical benefits - Gerald, Joe K.; Preedy, Victor R.; Watson, Ronald R. [ (Ronald Ross)] (Nutrition and health, 2011)
Nutrients, Dietary Supplements, and Nutriceuticals: Cost Analysis Versus Clinical Benefits" provides the most current, concise, scientific appraisal and economic analysis (costs vs. benefit) of nutritional supplements and bioactive components (nutriceuticals) of foods in improving the quality of life. It fills a much-needed gap to have a single volume provide a synopsis of cost analysis of dietary supplements and nutritional products as well as therapies for treatment and prevention of disease. Chapters include emerging fields of science and important discoveries relating to early stages of new nutriceuticals in cancer prevention, prior to clinical trials